MALE AND FEMALE STUDENTS’ PERCEPTIONS TOWARD THE IMPLEMENTATION OF VIDEO CONFERENCE AS A DISTANCE LEARNING MEDIA THAT ENHANCES TEACHERS’ PRODUCTIVITIES - Yelis Bintang Permatasari (JALL (Journal of Applied Linguistics and Literacy), 2018)
This paper reports the implementation of video conference as a distance learning media that enhances teachers’ productivities in teaching English in a state high school in Tasikmalaya, West Java.  To give much greater size sample, this study took two sample classes with the overall fifty-six students participated in this study by using cluster sampling technique. This study employed a qualitative research design focusing on the survey study method. A self-administration of twenty questionnaires provided to identify the distinctions perceptions between male and female students thought. A depth information appear to be as important to gain more in-depth information and continuous responses to explore the advantages and its disadvantages of video conferencing that have been undertaken by interviewing the students. The findings revealed that despite some limitation, the teaching and learning process with video conferencing was successful, then male students appear more favorably and react positively compared to female students. By having more positive responses, video conferencing proven to enhance teachers’ productivities. More significantly, students argue on its advantages and disadvantages of video conferencing that was undertaken by interview. The advantages of video conference such as video conference could connect between teachers and students wherever they are, video conference alow them to access lessons with teachers separately, video conference motivated, video conference enhances teachers’ role, responsibility, creativity, and students’ insights and learning experiences using new learning systems. Besides, video conference also has weaknesses or disadvantages when it is applied such as interactions limits, unstable internet connections, unclear sounds, video delay, and background noises. This can be noted that today learning and teaching process can benefit from using video conference as a distance learning media that teachers can used to improve their productivity, as well as substitution for teachers’ absences in the classroom, so that learning can be done, and teacher productivity maintained wherever they are. Keywords: Male and Female, Video Conference, Distance Learning Media,                     Teachers’ Productivities.